Image of Higher Educational Institutions: Features of Perception by Graduating Class Students - V. A. Sagaidak; A. L. Kuzevanova; O. Yu. Yabloskikh (Высшее образование в России)
The article is devoted to the problem of forming the image of higher educational institutions in the conditions of increasing competition in the regional market of educational services, as well as between regional and metropolitan educational institutions. The purpose of the study is to identify the features of perception of a higher education organizations image by pupils of graduating classes. The results of online survey of high school pupils from Volgograd and Volzhsky and the series of in-depth interviews with graduate pupils are presented. The results of the study demonstrate the subjective perception by potential applicants of the essence of image of higher educational institutions, limited by the specifics of their social experience and status of schoolchildren. The key components of the image of universities, according to Volgograd pupils, include the image of educational services and teaching staff, social and visual image, that corresponds to the priority of the activities of educational organizations and correlates with the results of All-Russian and regional sociological studies. The effectiveness of Internet resources as a source of information about universities, that was revealed by the results of a survey of pupils, reflects the general trends of the digital society, and the high importance of personal contacts reflects the specifics of the regional image of educational institutions. The current image of the main universities of Volgograd is characterized by reflects of the final grades quite positively, however, a third of the study participants found it difficult to assess the key image components, that indicates the need to improve the efficiency of educational organizations in their formation. At the same time, the most relevant is the construction of a positive image of the teaching staff and the internal image of local educational institutions, reflecting the specifics of their socio-psychological climate. The recommendations to improve the effectiveness of image-forming activities, that were proposed by the authors, are related to the expansion of the representation of universities in the Internet space, the involvement of teachers and opinion leaders from among the student community as content authors, as well as the development of interactive communication with potential applicants.